1988
DOI: 10.1073/pnas.85.2.622
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization histochemistry and immunocytochemistry reveal an increase in spinal dynorphin biosynthesis in a rat model of peripheral inflammation and hyperalgesia.

Abstract: Dynorphin, an opioid peptide, is thought to play an important role in the modulation of nociceptive neural circuits at the level of the spinal cord. In a model of peripheral inflammation and hyperalgesia, an oligodeoxyribonucleotide probe complementary to a portion of preprodynorphin mRNA and antisera to dynorphin A-(1-8) were used to localize changes in dynorphin mRNA and peptide to individual spinal cord neurons. Intraplantar injection in rats of complete Freund's adjuvant resulted in edema and hyperalgesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
94
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(103 citation statements)
references
References 19 publications
(37 reference statements)
9
94
0
Order By: Relevance
“…Peripheral tissue inflammation has also been shown to produce a robust increase in dynorphin peptide in the spinal cord (Iadarola et al, 1988a;Millan et al, 1988;Ruda et al, 1988). This increase is preceded by an increase in the levels of PPD mRNA coding for this opioid peptide product (Iadarola et al, 1988a).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Peripheral tissue inflammation has also been shown to produce a robust increase in dynorphin peptide in the spinal cord (Iadarola et al, 1988a;Millan et al, 1988;Ruda et al, 1988). This increase is preceded by an increase in the levels of PPD mRNA coding for this opioid peptide product (Iadarola et al, 1988a).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that c-fos mRNA increases within 30 min following injection of an inflammatory agent and precedes increased PPD mRNA expression that is first observed at 4 hr . Whereas unilateral inflammation has been shown to produce a robust increase in dynorphin gene expression (Iadarola et al, 1988a,b;Ruda et al, 1988;Draisci and Iadarola, 1989;Noguchi et al, 1991), relatively small increases in PPE mRNA were seen with RNA blot hybridization (Iadarola et al, 1988b;Draisci and Iadarola, 1989) and in situ hybridization (Noguchi et al, 1992). Both PPD mRNA and PPE mRNA have been shown to increase within some spinal dorsal horn neurons that also exhibit increases in Fos-LI after inflammation (Noguchi et al, 199 1, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory pain is characterized by up-regulation of spinal dynorphin (Nahin et al, 1989;Ruda et al, 1988), CGRP and SP in the DRG and spinal cord (Donnerer et al, 1992(Donnerer et al, , 1993, and the NK-1 receptor within the spinal cord (Abbadie et al, 1996(Abbadie et al, , 1997Trafton et al, 1999). Moreover, increased distribution of neurons showing NK-1 receptor internalization was observed following noxious stimulation, with noxious stimulation induced NK-1 receptor internalization in deep dorsal horn neurons, instead of only in lamina I neurons as observed in untreated controls (Abbadie et al, 1997).…”
Section: Discussionmentioning
confidence: 99%